2011
DOI: 10.1021/bi200130r
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nitric Oxide with Catalase: Structural and Kinetic Analysis

Abstract: We present the structures of bovine catalase in its native form and complexed with ammonia and nitric oxide, obtained by X-ray crystallography. Using the NO generator 1-(N,N-diethylamino)diazen-1-ium-1,2-diolate, we were able to generate sufficiently high NO concentrations within the catalase crystals that substantial occupation was observed despite a high dissociation rate. Nitric oxide seems to be slightly bent from the heme normal that may indicate some iron(II) character in the formally ferric catalase. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 81 publications
2
39
0
2
Order By: Relevance
“…As Reaction 3 shows, the enzyme protects the cells by converting H 2 O 2 into water and O 2 [79]. The proposed mechanism occurs in two steps and involves the ferryl intermediates [80]. In the first step the enzyme reacts with H 2 O 2 to form compound I.…”
Section: Interaction Of H2s With Enzymesmentioning
confidence: 99%
“…As Reaction 3 shows, the enzyme protects the cells by converting H 2 O 2 into water and O 2 [79]. The proposed mechanism occurs in two steps and involves the ferryl intermediates [80]. In the first step the enzyme reacts with H 2 O 2 to form compound I.…”
Section: Interaction Of H2s With Enzymesmentioning
confidence: 99%
“…The result is that the NO undergoes recombination with the metal in the latter case more readily than it does diffusion away to give net ligand labilization. This scheme has been confirmed by a number of ultrafast flash photolysis studies that observed the geminate pair directly and have probed the influence of protein structure (as modified by site-directed mutagenesis) on the efficiency and dynamics of the ligand escape relative to recapture [63,66,68,78,79].…”
Section: Pormentioning
confidence: 73%
“…The cyclic voltammogram of the aryloxide 7 is shown in Figure 5. The observed first reversible oxidation at E o ' = +0.59 V vs. the Fc/Fc + couple, to generate the [7] + cation, is 20 mV higher than that required to oxidize the related [T(pOMe)PP]Ru(NO)Cl under similar experimental conditions, [36] reflecting the overall better electron-donating property of the aryloxide ligand compared with chloride. The cyclic voltammogram also shows a second reversible oxidation at E o ' = +1.04 V, and a quasi-reversible reduction at E pc = -1.66 V. The cyclic voltammograms of the alkyl carboxylate compounds 1-3 and 8 are shown in Figure 6.…”
Section: Electrochemistrymentioning
confidence: 90%
“…Nitric oxide binds to some of these latter complexes to inhibit their function. [7,8] The (por)M(NO) moieties containing the group 8 metals are, indeed, interesting from an electrochemistry standpoint, as all three por/M/NO fragments are electroactive. Despite the biological relevance of the ferric nitrosyl O-liganded compounds, it is surprising that only a few such (por)Fe(NO)(O-ligand) complexes have been reported in the literature; [9,10] however, these complexes are unstable in solution releasing the weakly bound {RuNO} 6 complexes.…”
Section: Introductionmentioning
confidence: 99%